Ethanol from lignocellulosic biomass: techno-economic performance in short-, middle- and long-term - Hamelinck, C.N.; Van Hooijdonk, G.; Faaij, A.P.C.
The state of the art of hydrolysis-fermentation technologies to produce ethanol from lignocellulosic biomass, as well as developing technologies, is evaluated. Promising conversion concepts for the short-, middle- and long-term are defined. Their technical performance was analysed, and results were used for economic evaluations. The current available technology, which is based on dilute acid hydrolysis, has about 35
Keywords: ETHANOL; HYDROLYSIS; ECONOMICS